SOME ISSUES OF THE FUNCTIONAL HEALTH AMONG MOSCOW SCHOOLCHILDREN - O. V. Andreeva; K. G. Gurevich; A. D. Fesyun; V. V. Odintsova; D. A. Pustovalov; A. N. Oranskaya; E. A. Dmitriyeva; E. V. Okunkova (Кубанский научный медицинский вестник)
The problem of schoolchildren's health functional reserves in the last decade gained global, epidemic scale. The researchers of this problem considering various risk factors affecting the health of the functional reserves of that category of persons, the most common of which is the development of excess body weight, ranging from the simple overeating and inactivity, genetic problems to complex mechanisms of metabolic disorders in tissue and molecular levels. We also know that there are certain age periods when obesity occurs most often from the moment of birth to one year, in 5-6 years and puberty. Multi-year tendency in the number of persons with reduced functional reserves health among schoolchildren entails the subsequent decline of health in all age groups and further affects the quality of human resources, reproduction of generations. Since the early 1990s, there is a tendency to deterioration of indicators characterizing the state of health, in particular, the growth of psychosomatic illness of adolescents and youth, especially in the final year of big towns and industrial cities. Meanwhile, the current data on the prevalence of obesity in Russia, as well as age-specific statistics on this disease around the world virtually non-existent. The purpose of this study was to examine age and gender-specific functional health reserves among schoolchildren, due to the urgency of upgrading health programs at the school level, aimed at disease prevention.